If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a * 3y + 3a = 0 Reorder the terms for easier multiplication: 2 * 3a * y + 3a = 0 Multiply 2 * 3 6a * y + 3a = 0 Multiply a * y 6ay + 3a = 0 Reorder the terms: 3a + 6ay = 0 Solving 3a + 6ay = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '3a'. 3a(1 + 2y) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(1 + 2y)' equal to zero and attempt to solve: Simplifying 1 + 2y = 0 Solving 1 + 2y = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2y = 0 + -1 2y = 0 + -1 Combine like terms: 0 + -1 = -1 2y = -1 Add '-2y' to each side of the equation. 2y + -2y = -1 + -2y Combine like terms: 2y + -2y = 0 0 = -1 + -2y Simplifying 0 = -1 + -2y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
a = {0}
| h^3+8h^2-h-8=0 | | -10.3x=82.4 | | 9w^2+42w+49= | | 100x^2-90x+20=0 | | 11(t-2)+3t=7(2t+3)-11 | | 2x-5+7x=6+3x+10 | | 21x^2+58x+21=0 | | (5n+8)(2n-1)=0 | | 2(x+6)+82=9x-7(x+2) | | 5w^2-15w+12=2 | | -4x+3(3x-4)=1-8x | | 42-(3y+2)=2(y+2)+4y | | -2t^2-3t+9=0 | | 35x-10=23x+5 | | 7y+2y=-38-11 | | 6x-3=16x+33 | | -3y+7=-5+4y | | 81c^2-36c+4= | | -88=10x+2 | | (2x+1)+(x-1)= | | -2a+3+3a=13-27 | | 16r^2=36+36r | | 8s^2=12+20s | | x+298=18 | | 6x^5-12x^3+6x=0 | | 8s+6t-(-5s)-2t= | | 4x+12=11+3x | | 2(3x-1)=-3(4-2x) | | 5(w-7)=w+4(w+1) | | 5+x=-2x+14 | | y+[-16]=-12 | | -0.25x+0.5-4= |